Răspunsuri

2014-05-06T00:13:52+03:00
A) {2x-3y=13             ·(-2)⇒   {-4x+6y=-26
    {4x-y=8                               {4x-y=8   se reduce x⇒      6y-y=-26+8
5y=-18 ⇒y=-18/5 ⇒ y=-3,6
din 4x-y=8⇒  4x+3,6=8   ⇒   4x=8-3,6   ⇒4x=4,4  ⇒x=4,4/4⇒   x=1,1
b) {4x-2y=-2                                {4x-2y=-2
    {3x+y=-9     inmultim cu 2⇒    {6x+2y=-18   ⇒ 4x+6x=-2-18
10x=-20⇒     x=-20/10⇒    x=-2
din 3x+y=-9⇒    3·(-2)+y=-9⇒  -6+y=-9⇒    y=-9+6
y=-3
c) {2x+y=0                                 {2x+y=0
    {x-3y=7     inmultim cu -2⇒    {-2x+6y=-14     ⇒6y+y=-14
7y=-14⇒   y=-14/7⇒    y=-2
din 2x+y=0  ⇒  2x=-2⇒    x=-2/2⇒⇒⇒ x=-1